Objective Economic Pressures, Livelihood Strategies, and Subjective- Economic Welfare of Survivor’s Families of Sunda Strait Tsunami in Banten: Objective Economic Pressures, Livelihood Strategies, and Subjective- Economic Welfare of Survivor’s Families of Sunda Strait Tsunami in Banten - Fadilla Marrizka Laily; Euis Sunarti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
This research is part of umbrella study entitled “The Impact of the 2018 Sunda Strait Tsunami on Family Socio-Economic Vulnerability and Achievement of SDGs Welfare”. This study aims to analyze family characteristics, objective economic pressures, livelihood strategies, and subjective-economic welfare for survivors of Sunda Strait Tsunami disaster in Banten. The research method used is a cross-sectional study involving 60 samples selected by simple random sampling. Data collection was carried out in March 2021 (27-month post disaster). Data analysis used descriptive tests, correlation tests, and logistic regression tests. The regression test results showed that the wife's age, husband's age, income per capita, and objective economic pressure had a significant effect on subjective economic welfare. The results of the cumulative probability analysis show that families with low welfare categories have the opportunity to increase their subjective economic welfare by 0.989 times, while families with high welfare have the opportunity to increase their subjective economic welfare 6,632 times compared to families with low welfare categories. Migration of residence from coastal areas to permanent residences in the middle of plantations does not make families change their livelihoods or explore new skills in earning a living to increase income.